Mathematical Modeling for Women$1 (Bs Healths Collaborative Workshop for Women in Mathematical Biology - Ford Versypt, Ashlee N.; Segal, Rebecca A.; Sindi, Suzanne S.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
The purpose of this work is to focus mathematical modeling on issues affecting women$1 (Bs health. Working in six collaborative teams, researchers developed new mathematical models to address questions in a range of application areas. Topics include HIV, oral contraceptives, blood clotting, breast cancer, neonatal respiration, and outbreak forecasting. The work is the result of newly formed collaborative groups begun during the Collaborative Workshop for Women in Mathematical Biology hosted by the Institute of Mathematics and its Applications and UnitedHealth Group Optum in June 2022. This is an open access book.s
Collaborative Workshop for Women in Mathematical Biology: Mathematical Modeling for Women$1 (Bs Health -- Extended-Release Pre-Exposure Prophylaxis and Drug-Resistant HIV -- A Survey of Mathematical Modeling of Hormonal Contraception and the Menstrual Cycle -- Studying the Effects of Oral Contraceptives on Coagulation Using a Mathematical Modeling Approach -- Deconstructing the Contributions of Heterogeneity to Combination Treatment of Hormone Sensitive Breast Cancer -- Towards a Mathematical Understanding of Ventilator-Induced Lung Injury in Preterm Rat Pups -- Estimation of Time-Dependent Transmission Rate for COVID-19 SVIRD Model Using Predictor-Corrector Algorithm -- Index.s
Keywords: Biomathematics; Mathematical models; Mathematical and Computational Biology; Mathematical Modeling and Industrial Mathematics